The Not-So-Curious Case of Low Political Participation in Romania - Tufiş, Claudiu D. (Calitatea Vieții, 2014)
This paper analyzes the insufficiently developed political participation in post-communist Romania, focusing on the pre-requisites of political participation, and on how these are acting as inhibitors for political involvement from the citizens. The prevalence of intolerance, the lack of trust in other people and in the institutions of the state, the absence of points of access to the political system and an insufficiently developed culture of protest are all factors that contribute to determining Romanians to avoid political participation. Data on voting, volunteering, and protesting demonstrate the underdevelopment of political participation in Romania.